Research on the Import Skills Based on Micro-Teaching in Junior Middle School - Cui, Yuhao; Sun, Yuhang; Zhao, Wenxu; Zhang, Ziyu; Sun, Lin (Advances in Social Sciences Research Journal, 2025)
Attaching importance to the improvement of teachers’ skills and qualities and strengthening the construction of teachers’ ranks are the foundation of consolidating education and the source of education. As a new training method of teaching skills, micro-teaching provides support for the cultivation of classroom teaching skills of normal university students and promotes the implementation of teaching skills training of normal university students. At present, in the actual teaching, teachers’ import skills still need to be strengthened. Therefore, this paper selects the import skills in micro-teaching, combined with the specific teaching content cases in junior high school chemistry, to explore the application of import skills.